1987
DOI: 10.1152/jappl.1987.63.4.1463
|View full text |Cite
|
Sign up to set email alerts
|

Fetal breathing, sleep state, and cardiovascular responses to graded anemia in sheep

Abstract: Graded anemia was produced for 2 h in 10 unanesthetized fetal sheep by infusing plasma in exchange for fetal blood. This reduced the mean fetal hematocrits during the 1st h of anemia to 19.7 +/- 0.5% [control (C) = 28.2 +/- 1.1%] for mild anemia, 17.4 +/- 0.9% (C = 30.0 +/- 1.1%) for moderate anemia, and 15.1 +/- 1.0% (C = 29.2 +/- 1.3%) for severe anemia. The respective mean arterial O2 contents (CaO2) were 4.46 +/- 0.20, 3.89 +/- 0.24, and 3.22 +/- 0.19 ml/dl. Mean arterial PO2 was reduced significantly (by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, the value is not lower than that of chronically catheterized fetuses [19], which are most widely used as experimental models in fetal physiological studies. Moreover, it has been reported that fetal breathing activity was not affected by mild anemia [20]. Therefore, it is unlikely that the incidence of breathing movements is affected by the low hemoglobin concentration in this study.…”
Section: Discussionmentioning
confidence: 57%
“…However, the value is not lower than that of chronically catheterized fetuses [19], which are most widely used as experimental models in fetal physiological studies. Moreover, it has been reported that fetal breathing activity was not affected by mild anemia [20]. Therefore, it is unlikely that the incidence of breathing movements is affected by the low hemoglobin concentration in this study.…”
Section: Discussionmentioning
confidence: 57%
“…Preclinical studies provide evidence for a brainstem‐mediated response to acute hypoxia in utero resulting in a reduction in fetal breathing movements, a reduction in fetal heart rate and centralisation of combined cardiac output mediated by increased peripheral vascular resistance (Bartelds et al., 1993 ; Boddy et al., 1974 ; Giussani et al., 1993 ; Itskovitz et al., 1991 ; Koos et al., 1987 ). The role of the brainstem in this adaptive hypoxic response has been elucidated in fetal sheep studies in which the brainstem was transected (Dawes et al., 1983 ); without a functional brainstem, late‐gestation fetal sheep increased fetal breathing movements and nuchal muscle activity in response to an acute hypoxic episode (Dawes et al., 1983 ).…”
Section: Fgr and Developmental Deficits In The Brainstem Structurementioning
confidence: 99%
“…The oxygen content is reduced by decreasing the fetal hematocrit level. Isovolemic anemia is produced by an exchange transfusion method in which maternal plasma is infused into the fetal vein while simultaneously withdrawing the same volume of fetal blood from the fetal artery Hypobaric high‐altitude hypoxia.…”
Section: Hypoxia Classificationmentioning
confidence: 99%